2017
DOI: 10.17851/2237-2083.25.3.1183-1224
|View full text |Cite
|
Sign up to set email alerts
|

Representation and Processing of the Inflected Infinitive in Brazilian Portuguese: an eye-tracking study

Abstract: Este estudo examina a representação sintática e as características de processamento de sujeitos nulos de orações infinitivas flexionadas em português brasileiro (PB). Após revisão de parte da literatura atual sobre a Teoria do Controle e discussão das peculiaridades da diacronia do PB, o artigo apresenta um experimento envolvendo rastreamento ocular que comprova que a interpretação controlada do sujeito da infinitiva flexionada é não apenas real psicologicamente, mas também a opção preferida numa tarefa em que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 31 publications
(53 reference statements)
1
13
0
2
Order By: Relevance
“…Schooling may reinforce the use of inflection, but it does not determine where speakers will use it. Modesto and Maia (2017) have shown exactly that: the normal use of NI by "educated speakers of BP" is in control structures, something frowned upon by school grammar. Their experiment shows that BP speakers do not use the grammatical system taught in school when reading inflected infinitives.…”
Section: Introductionmentioning
confidence: 87%
See 4 more Smart Citations
“…Schooling may reinforce the use of inflection, but it does not determine where speakers will use it. Modesto and Maia (2017) have shown exactly that: the normal use of NI by "educated speakers of BP" is in control structures, something frowned upon by school grammar. Their experiment shows that BP speakers do not use the grammatical system taught in school when reading inflected infinitives.…”
Section: Introductionmentioning
confidence: 87%
“…BP speakers have native judgments on the distribution of NI, and those judgements are not what one would expect if those speakers were following the grammar taught in Brazilian schools, as shown by the experimental results of Modesto and Maia (2017). It is then concluded that results already obtained by the study of NI are scientifically interesting.…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations